Moral Education, Democratic Citizenship, and Religious Authority - Walzer, Michael (Journal of law, religion and state, 2012)
I have two purposes in this essay: first, to argue that morality forms a central part of a liberal education and to say something about how it is properly taught; second, to argue more specifically that the moral virtues required by democratic citizenship, and the rights and obligations that citizenship entails, should figure in school curricula, and then to consider the conflicts with religious authority that this is sure to produce.